Playing by the Rules? An Investigation of the Relationship Between Social Norms and Adolescents' Hate Speech Perpetration in Schools. Issue 21 (November 2022) - Wachs, Sebastian; Wettstein, Alexander; Bilz, Ludwig; Krause, Norman; Ballaschk, Cindy; Kansok-Dusche, Julia; Wright, Michelle F.
Hate speech is often discussed and investigated as an online phenomenon, while hate speech among adolescents in the real world (e.g., in schools) has rarely been researched. Consequently, not much is known about potential interpersonal correlates and theoretical frameworks that might help us better understand why adolescents engage in hate speech in offline environments. To add to the literature, this study investigates hate speech perpetration among young people by utilizing the Social Cognitive Theory; more specifically, the association between witnessing and perpetrating hate speech in schools, and whether this relation is weakened or strengthened by anti-hate speech injunctive norms and deviant peer pressure. The sample consists of 1719 young people (45.1% boys, 53.6% girls, 1.3% gender diverse) between 11 and 18 years old ( M age = 13.96; SD = .98) from 22 schools in Switzerland. Self-report questionnaires were administered to measure hate speech involvement and adolescents' perception of social norms (i.e., anti-hate speech injunctive norms and deviant peer pressure). Multilevel regression analyses revealed that witnessing and perpetrating hate speech were positively associated. Moreover, injunctive anti-hate speech norms were negatively related and deviant peer pressure positively related to hate speech perpetration. Finally, increasing levels of injunctive anti-hate speech norms weakened the relation between witnessing and perpetrating hate speech, whereas higher levels of deviant peer pressure strengthened this association. The findings demonstrate that the Social Cognitive Theory is a useful framework for understanding hate speech perpetration in schools. The results also highlight the importance of taking into account social norms and interpersonal relationships (e.g., within the class) when designing anti-hate speech prevention programs and not focusing solely on intrapersonal factors.